Pengaruh Perputaran Kas, Piutang, Persediaan, Siklus Konversi Kas, dan Perputaran Aktiva Tetap Terhadap Profitabilitas pada Perusahaan Sub Sektor Farmasi yang Terdaftar di Bursa Efek Indonesia Periode 2020-2024. - Kurnia Tri; Rudi Kurniawan; Linda Ayu Oktoriza; Diana Puspitasari (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
The purpose of this study is to examine how the profitability (ROA) of pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange between 2020 and 2024 is affected by cash turnover, accounts receivable turnover, inventory turnover, cash conversion cycle, and fixed asset turnover.  The research is conducted to determine how the effectiveness of working capital management and asset utilization contributes to enhancing a company’s financial performance, particularly in producing profit. Using secondary data from pharmaceutical companies' yearly financial statements, this study employs a quantitative methodology.  Purposive sampling was used to pick the sample, which included 13 businesses with 65 observations during a five-year period.  Descriptive statistical analysis and traditional assumption tests are among the tests. Using SPSS 26's multiple linear regression analysis to look at how each independent variable affects profitability. The findings demonstrate that the cash conversion cycle, inventory turnover, and accounts receivable turnover all significantly and favorably impact profitability.  In contrast, monetary turnover and fixed asset turnover do not demonstrate a substantial influence.  Concurrently, the model's five variables are shown to have a considerable impact on profitability, with an R2 value of 0.523, which indicates that these factors account for 52.3% of the variation in profitability.  These data demonstrate that the effectiveness of managing receivables, inventory, and the cash cycle plays an essential role in boosting the profitability of pharmaceutical firms.